Perlindungan Hukum bagi Pemilik Tanah Girik yang Belum Mendaftarkan Tanahnya - Marlyn Aghustin Ma'i; B.F Sihombing (Jurnal Hukum Lex Generalis, 2025)
There are still major challenges in its implementation, such as lack of public awareness of the importance of land registration, lack of socialization from the authorities, and administrative barriers faced by the community, especially in rural areas. The existence of this time limitation also raises new concerns regarding land disputes, especially if there is a conflict between the owner of the girik and the owner of the valid certificate. Therefore, this study is very important to dig deeper into the issue of the deadline for registration of customary land after the entry into force of government regulation number 18 of 2021. This study aims to understand how the policy is implemented, its impact on the renewal of the land system, as well as its relevance in providing legal certainty to citizens. Therefore, this research is expected to provide real contributions and benefits in encouraging fairer and more effective land reform in Indonesia. Legal protection for owners of girik land who have not registered their land after the deadline for land registration according to PP number 18 of 2021 ends, they still get legal protection from the state, because the owner of girik land is still given the opportunity to register his girik land, but the basis for registering his land is not with written evidence in the form of girik, but with a mechanism for applying for recognition of land rights provided that the land has been physically controlled by the person concerned for 20 (twenty) years or more continuously, without any objection from any party (the land is not in dispute).